Service quality expectations and evaluations of Hotel customers-an exploratory study on Hotel services marketing - Cantez, Aylin (My University, 1995)
unknown
Keywords: KALİTE-HİZMET KALİTESİ-OTELLER; OTELCİLİK-PAZARLAMA